Piped water schemes for rural water supply in Zimbabwe: reviving a forgotten chapter.: a case of Rusere piped water scheme in Zaka district - Muneri, Desire (Midlands State University, 2017)
The main thrust of the research was to analyse the revival of the once defunct Rusere Piped Water Scheme. The study also sought to bring out the opportunities and challenges that are faced in the revival of community owned and managed schemes. Qualitative research approach was used to carry out the research and data collection tools included questionnaires and interviews from key informants such as the DWSSC and local leaders. Field observations were also carried out to ascertain the impact of the piped water scheme on the community. The researcher discovered that the scheme had brought considerable benefits to the Rusere Community such as the availability of safe water within a safe distance and in right quantities. There has also been improvement in community participation, community based management of local resources has been boosted and women participation and empowerment have been realised through the scheme. The research also highlighted the challenges faced during the rehabilitation and operation of the scheme and these include lack of funds for expansion and political patronage on the schemes. After the analysis of the data from the field, the researcher discussed possible measures that can be employed to make the rural piped water schemes a sustainable water supply system. The formation of Public-Private Partnerships in rural water supply proved to be the way to go in realising safe water supply in rural communities.